Functional Food Innovation of Yogurt From Breadnut Seeds (Artocarpus camasi): Basic Formulation and Quality Analysis - Sintyadewi, Putu Rima; Yoga , Wahyu Krisna (Jurnal Pijar Mipa, 2024)
Yogurt is one of the dairy products fermented by lactic acid bacteria (LAB) that has long been recognised as a functional food. Breadnut seeds (Artocarpus camansi) have the potential as prebiotics to stimulate LAB growth during yogurt fermentation so that the functional effects of this plant-based yogurt can be optimised. In addition, breadnut seeds are also reported to contain essential amino acids and have high antioxidant activity. The purpose of this study was to determine the best formulation of breadnut seed dairy and LAB type (L. bulgaricus and S. termophilus) adjusted to the quality standards of SNI (2981-2009) yogurt, including pH test, total titratable acid, proximate test (water, fat, protein, and ash content), and microbiological test (total LAB). The design used in this study was a completely randomized design (CRD) with two factorials. The first factor was the formulation of breadnut seed dairy with UHT milk with four treatments, namely P1 (70%:30%), P2 (50%:50%), P3 (30%:70%), and P4 (100% breadnut seed dairy). The second factor is the type of LAB stater with three treatments, namely S1 (L. bulgaricus), S2 (S. thermophilus), and S3 (combination of both). The recommended formulation for breadnut seed yogurt is 100% breadnut seed dairy with a combination of L. bulgaricus and S. thermophilus staters (P4S3). The P4S3 formulation has met the quality standards of yogurt by SNI 2981:2009, including ash content, fat content, protein content, total acid and pH, and total LAB. The P4S3 formulation has an advantage over other formulations by having a lower fat content of 2.37% and a higher protein content of 3.71% compared to animal milk. Breadnut seed yogurt with P4S3 formulation contains a total LAB 3.02 x 107, which has potential as an alternative functional drink.